Avian Navigation: Pigeon Homing as a Paradigm - Wallraff, Hans G. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
How migratory birds can navigate home from their wintering grounds to their breeding sites over hundreds and thousands of kilometres has been an admired mystery over more than a century. Profound advances towards a solution of this problem have been achieved with a model bird, the homing pigeon. This monograph summarizes our current knowledge about pigeon homing, about the birds' application of a sun compass and a magnetic compass, of a visual topographical map within a familiar area and -- most surprisingly -- of an olfactory map using atmospheric chemosignals as indicators of position in distant unfamiliar areas.